Accumulation of human pharmaceuticals and biotransformation enzymes in fish from two areas of the lower Rio de la Plata Basin - Rojo, M. (2020)
The accumulation of four human pharmaceuticals active compounds (HPhAC) in the muscle of four fish species of the Rio de la Plata Basin were assessed regarding the compound logP and pKa, and fish trophic levels. For Prochilodus lineatus, accumulation was compared to hepatic biotransformation enzymes and fish from two sampling areas with different urbanization degree. Species were the detritivore Prochilodus lineatus, the omnivores Megaleporinus obtusidens and Pimelodus maculatus, and the piscivorous Salminus brasiliensis. Sampling areas were the Inner Rio de la Plata Estuary (RLP), in front of the Buenos Aires Metropolitan Area, and at the Lower Uruguay River (URU), a relatively unpopulated area. Carbamazepine, atenolol, enalapril, and sildenafil concentrations in fish muscle were analyzed by HPLC-MS. EROD, BROD, and GST activities were measured in P. lineatus liver. Average (maximum) concentrations and detection frequency were: Atenolol 24.4 (69.4) μg kg-1, 60%; carbamazepine 5.5 (45.8) μg kg-1, 19%; enalapril 7.0 (56.9) μg kg-1, 28%; sildenafil 17.1 (71.6) μg kg-1, 56%. Enalapril and sildenafil detection in fish was first-time reported. Atenolol and carbamazepine concentrations were positively correlated. No correlation was observed between HPhAC accumulation and logP or pKa. A potential biomagnification trend was observed for atenolol, showing higher accumulation in S. brasiliensis. HPhACs accumulation was higher for P. lineatus collected at URU, but GST and BROD were significantly higher for individuals sampled at RLP and were positively correlated. A significant negative correlation was observed for enalapril and BROD. The study contributes to the knowledge of the accumulation of HPhACs in fish.